Labor duration and maternal-neonatal short-term outcomes in nulliparous women with vaginal delivery receiving intravenous normal saline and intravenous dextrose - Farnaz Sahhaf; Tahereh Alizadeh Ghalehlar (Mashhad University of Medical Sciences, 2019)
Introduction: Causes of prolonged labor have been extensively studied. It has been previously proved that glucose is the main energy substrate for pregnant uterus. It is assumed that intravenous dextrose may shorten the length of labor; however there is no enough evidence in this regard. This study was performed with aim to compare labor duration and maternal-neonatal short-term outcomes in nulliparous women with vaginal delivery receiving intravenous normal saline or dextrose. Methods: In this double-blind randomized clinical trial, 300 nulliparous, singleton women in active phase of vaginal delivery were studied in Tabriz Alzahra educational center in 2013. The women were simple randomly divided into three similar groups: receiving intravenous normal saline 125 ml/h, receiving intravenous dextrose 5% 125 ml/h and control. Data were collected by maternal- pregnancy characteristics questionnaire (based on examination and mother's file) and fetal-neonatal outcomes questionnaire (based on examination and neonate's file). Data were analyzed using SPSS software (version 15), and one way ANOVA, Tukey post hoc test, Chi-square or Fisher exact test. P<0.05 was considered statistically significant. Results: Mean duration of first stage of labor was similar in three groups (p = 0.69); however, mean duration of second stage (p<0.001), third stage (p<0.001) and total length of labor (p<0.001) were significantly lower in dextrose group. Prolonged labor (>12h) was significantly more common in control group (39%) than in dextrose group (5%) and normal saline group (10%) (p<0.001). Maternal and neonatal short-term outcomes were not significantly different between three groups (P>0.05). Conclusion: Total duration of labor in nulliparous term women with active vaginal labor is reduced by intravenous injection of 125 ml/h dextrose 5%.